Optimal Rate of Printing of 3D Printed Concrete Columns and Walls to Avoid Buckling. Issue 1 (September 2020) - Phadnis, K P; Shariff, M N; Menon, D
Abstract: Extrusion based construction of concrete structures has been identified as one of the alternative construction technologies which reduces the construction costs, delays in construction and the material consumption. The most attractive feature of 3D printed constructions is the ease of developing intricate forms and shapes (which otherwise require skilled manpower). Since this is a relatively new technology, not much research has been done with regard to its structural performance and stability. One of the major concerns is the possibility of buckling (under its self-weight) of the column or wall during the extrusion process. This sets a limitation of the acceptable height, thickness and rate of extrusion process. In this study simple ways (second order analysis using matrix methods) have been explored to determine the critical height and the optimal rate of extrusion. Matrix methods have inherent limitations due to the simplification adopted by ignoring the higher-order terms in Taylor's series. The study uses the evolution of modulus of elasticity of concrete as proposed in literature. The analysis method has been validated using pertinent buckling tests reported in literature. Parameters such as modulus of elasticity and length are considered to determine the critical height to thickness of the wall and the optimal rate of extrusion. The problem is solved using the MATLAB software. This method requires minimal input from the user such as material properties, geometry and printing speed. The analysis method used in this study provides a useful design tool to estimate the limiting parameters of the structural walls and columns manufactured through the process of 3D printing.